DENTAL PHANTOM DOLLS: A MEDIA INNOVATION IN TEACHING BRUSHING TEETH TO PRESCHOOL CHILDREN - Tedi Purnama; Rizki Sofian (JDHT Journal of Dental Hygiene and Therapy, 2023)
Dental health problems that many Indonesian people suffer from are dental caries. Poor dental and oral hygiene is one of the factors causing dental caries or dental and oral health problems. Dental and oral health education demonstration method of brushing teeth with phantom dolls can improve teeth brushing skills and dental and oral hygiene status in preschool children. Objective: to analyze the effectiveness of dental health promotion using dental phantom dolls media on brushing skills and dental hygiene status of preschool children. Method: design of this study was pre-experimental This study used a pre-experimental design with a pretest and posttest with two group design. This research was conducted in preschool children in Pondok Labu Village, Cilandak District, South Jakarta City. The sampling technique used purposive sampling as many as 60 students. The research instrument used an observation sheet to brush teeth to measure teeth brushing skills and dental and oral hygiene status was measured using a plaque free score index. The dental health promotion media used in the intervention group was a dental phantom dolls, while the control group used a flipchart. Data analysis used paired sample test, Wilcoxon and independent t-test. Results: The dental phantom dolls was effective in improving tooth brushing skills (p<0.001) and effective in improving the dental and oral hygiene status of preschool children (p<0.001). Conclusion: The dental phantom dolls is effective as a medium for promoting dental health in an effort to increase the tooth brushing behavior of preschool children.